A review of the preparation and prospects of amorphous alloys by mechanical alloying - Xian-jie Yuan; Yi-rui Zhang; Xuan-hui Qu; Hai-qing Yin; Shuai Li; Zhen-wei Yan; Zhao-jun Tan; Su-meng Hu; Yu-guo Gao; Peng-yan Guo (Journal of Materials Research and Technology)
The preparation of amorphous alloys typically involves rapid solidification from a molten state. Since 1980, when Yermo and Koch first achieved the amorphization of alloys by mechanical alloying (MA), researchers worldwide have developed a strong interest in this technique, which allows for the amorphization of alloy components in a non-equilibrium state at room temperature without the need for a liquid phase. MA has been widely applied in the fabrication of both equilibrium and non-equilibrium materials over the past few decades, and it remains a crucial technique for the production of amorphous alloys. This review selectively summarizes research on MA-produced amorphous alloys reported over the past two decades. It explores key issues of MA amorphization from the perspectives of both the mechanism of amorphization and the design of amorphous compositions through MA. The first section primarily elucidates commonly used methods for designing amorphous compositions at present, while the second section expounds on the transformation mechanism of MA amorphization. The third section summarizes the influence of alloy element additions on its properties, and the fourth section mainly illustrates the contribution of computational advancements to the exploration of amorphous mechanisms and the design of amorphous compositions. Finally, prospects for the development trend of preparing amorphous alloys through MA are discussed.